A novel switched-capacitor and fuzzy logic-based quadratic boost converter with mitigated voltage stress, applicable for DC micro-grid - Tekin, Hakan; Bulut, Kübra; Ertekin, Davut (Springer, 2022)
High-voltage and efficient power converter topologies equipped with the simple and practical controller circuits are necessary, especially for integration between the low-power and low-voltage renewable energy sources (RESs) like the photovoltaic (PV) arrays and the grid. These converters can be used widely in electrical vehicles (EVs) or charging stations, aquatic, medical, transportation application and other cases. This study proposes a switched capacitor (SC)-based quadratic boost converter (QBC) structure that provides high-voltage gain at low duty cycles equipped with the fuzzy logic control (FLC) technique. The output gain of the proposed converter is higher than a second-order step-up converter or a conventional QB circuit thanks to the presented switched-capacitor topology and the manipulation of the switches in conventional QBC. By using the second switch to the conventional QBC, the voltage stress across the main power switch will decrease that enhance the reliability and long-life of the converter. Since the SC block acts as an intermediate layer between the QB and load through the capacitors and diodes of this block, the voltage and current stresses of the power switches and diodes on the QB side are less than stresses for semiconductors for classical QB and boost converter. In this study, the proposed QBC and controller system are analyzed mathematically in detail and in MATLAB/SIMULINK environment. A 200 W prototype was developed in the laboratory to validate the proposed converter and computerized analysis. Finally, the theoretical and experimental results were compared and verified.
Keywords: Quadratic boost converter; Fuzzy logic controller; Switched-capacitor; High voltage gain